Neonatal seizures: clinical manifestations and etiology - Daisy Widiastuti; Irawan Mangunatmadja; Taralan Tambunan; Rulina Suradi (Indonesian Pediatric Society Publishing House, 2016)
Background Neonatal seizures or fits are signs of central ner- vous system (CNS) diseases, metabolic disorders, or other dis- eases disrupting the CNS. Neonatal seizures are poorly classi- fied, under-recognized and often difficult to treat. It is important to recognize the type of neonatal seizures that might be the only sign of a CNS disorder. Objective To recognize the type and etiology of neonatal sei- zures in several hospitals in Jakarta. Methods This was an observational case series study on full-term and preterm infants who had seizures during hospitalization in Cipto Mangunkusumo, Harapan Kita, and Fatmawati Hospitals between January-June 2005. Neonatal seizures were defined as seizures occurring in the first 28 days of life of a term infant or 44 completed weeks of the infant's conception age of preterm infant. Results There were 40 neonates who born within the study period and had seizures. Girls were outnumbered boys. Most neonates were full-term with birth weight of more than 2500 grams. Analy- ses were done on 38 neonates with epileptic and non-epileptic seizures, while the other two who had mixed clinical manifestation were not included. Most seizures occurred in the first 3 days of life (23/38). The most common type was focal clonic (12/14) followed by general tonic (11/24) and motor automatism or subtle (10/24). The most common etiology was hypoxic ischemic encephalopa- thy (HIE) (19/38) followed by metabolic disturbances, mainly hy- pocalcaemia (11/38). Conclusion Common types of seizures in neonates were focal clonic, general tonic, and motor automatism (subtle). The most common etiology was HIE followed by metabolic disturbances, mainly hypocalcaemia